(untitled) (Comunicação & Inovação, 2024)
This work aims to explore the concepts of journalistic information and disinformation through the analysis of productions present on the Comprova website. The investigation was carried out through bibliographical research for the theoretical production and content analysis of the articles produced by the website between November 8th and 15th, 2022. The contents extracted from the initiative’s website are inserted in a post-election context, with marked presence of disinformation pieces that aimed to discredit the results of the elections. Thus, the importance of content checking and verification projects that operated during the period is highlighted, helping to disseminate correct information. The conclusion of the research is that Comprova appropriates journalistic language to present misinformation and its various formats, demonstrating the importance of journalism in combating misinformation.